GREEN CHEMISTRY TRENDS IN THE CONTEXT OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT - Stetsenko, Nataliia; Bublienko, Nataliia (SWorld-Ger Conference proceedings, 2023)
The work considers the modern direction of development of chemistry and chemical technology - green chemistry. It is based on the fact that it is necessary to apply innovative methods of obtaining chemical compounds in order not to harm the environment ei